The Two Great Healing Traditions: Issues, Opportunities, and Recommendations for an Integrated First Nations Healthcare System in Canada - Grace Kyoon Achan; Rachel Eni; Kathi Avery Kinew; Wanda Phillips-Beck; Josée G. Lavoie; Alan Katz (Taylor & Francis Group, 2021)
The First Nations in Manitoba, Canada, are calling for active recognition and incorporation of holistic traditional healing and medicine ways and approaches by the mainstream healthcare system that has hitherto tended to ignore all but biomedical approaches. This request for recognition requires elaboration on areas of opportunity for collaboration that could positively influence both Indigenous and allopathic medicine. We discuss pathways to an integrated healthcare system as community-based primary healthcare transformation. A community-based participatory research approach was used to engage eight Manitoba First Nations communities. One hundred and eighty-three (183) in-depth, semi-structured key informant interviews were completed in all communities. Grounded theory guided data analysis using NVivo 10 software. We learned that increased recognition and incorporation of traditional healing and medical methods would enhance a newly envisioned funded health system. Elders and healers will be meaningfully involved in the delivery of community-based primary health care. Funding for traditional healing and medicines are necessary components of primary health care. An overall respect for Indigenous health knowledge would aid transformation in community-based primary health care. Recognition of and respect for traditional healing, healers, medicines, therapies, and approaches is also recommended as part of addressing the legacy and intergenerational impact of assimilative policies including Indian residential schools as the Truth and Reconciliation Commission of Canada has stated in its Calls to Action.